2017
DOI: 10.5194/hess-21-1439-2017
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics in hyper-saline aquifers: hydro-geophysical monitoring and modeling

Abstract: Abstract. Saline-freshwater interaction in porous media is a phenomenon of practical interest particularly for the management of water resources in arid and semi-arid environments, where precious freshwater resources are threatened by seawater intrusion and where storage of freshwater in saline aquifers can be a viable option. Saline-freshwater interactions are controlled by physico-chemical processes that need to be accurately modeled. This in turn requires monitoring of these systems, a non-trivial task for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…6.6. At this site, [16] investigated the flow dynamics associated with freshwater injection in a hypersaline aquifer through hydrogeophysical monitoring and modeling, using five 20 m deep boreholes ( Fig. 6.6b, c).…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…6.6. At this site, [16] investigated the flow dynamics associated with freshwater injection in a hypersaline aquifer through hydrogeophysical monitoring and modeling, using five 20 m deep boreholes ( Fig. 6.6b, c).…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…This site appears to be ideal for testing the MGS regularized inversion procedure, as the very high electrical conductivity of the aquifer makes the unsaturated/fully saturated soil interface a sharp electrical conductivity interface. [16]. c Layout and numbering of the boreholes Prior to the freshwater injection experiment, laboratory petrophysical measurements and different surface, in-hole, and cross-hole electrical resistivity surveys were carried out to characterize the background of unsaturated/saturated sedimentary succession dominated by sands.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Among the monitoring activities, time-lapse geophysical investigations played a specific role. The use of repeated geophysical measurements to highlight changes in the system is state of the art for several hydrological applications but is used relatively scarcely at contaminated sites, particularly during remediation activities [40,[45][46][47]. An ERT profile during pilot testing was acquired to verify the correct product spread in the first application area.…”
Section: Methodsmentioning
confidence: 99%
“…A more complex and data requiring approach is the one that make use of numerical models to deploy new characterization methods, for example, describing the linear and non-linear optimization approaches to manage seawater intrusion via numerical scenarios [144][145][146][147][148][149][150], or determining the long-term effects induced by pumping saline groundwater to feed desalination plants [151]. In addition, the employment of geophysical methods coupled with numerical models to quantify the aquifer salinization extension has been explored only in few studies [152][153][154][155], and only one reported the socio-economic aspects of SWI in the modeling procedure [156]. Finally, two studies have employed complex reactive transport models to quantify biogeochemical reactions induced by SWI [157][158][159].…”
Section: Data Handling Techniquesmentioning
confidence: 99%